The Importance of Training on Employee Performance at PT. Anaszaen, Karawang City, West Java, Indonesia - Firdaus, Ridwan Tho At; Hersusetiyati (Sinergi International Journal of Education, 2024)
In the era of globalization, companies' need for quality labor is increasing. Companies must be adaptive and improve their capabilities to compete. Human resources play an important role in achieving the company's goals. This study aims to determine the effect of training on employee performance at PT. Anaszaen Karawang, given the continued decline in annual performance.The research method used a descriptive quantitative survey with saturated sampling in 36 respondents of PT. Anaszaen. The data collection technique uses observation, interviews and questionnaires. Data analysis was carried out with descriptive statistics, simple linear regression, partial hypothesis test, determination coefficient, validity test, and reliability test using SPSS Version 23. The results of the hypothesis test showed that training had a positive and significant effect on employee performance (significance 0.000 < 0.05; t count 16.469 > t table 2.03224). The determination coefficient of 88.9% shows that training contributes 88.9% to employee performance, with 11.1% influenced by other factors that were not studied. Although the training is considered quite good, there are aspects that need to be improved, especially the trainees, training methods, and work quality.